Structural and optical characteristics of dysprosium-doped zinc zirconate nanocomposites - Musembi, Michael K.; Dejene, Francis B.; Ahemen, Iorkyaa (Optica Publishing Group, 2020)
Zinc zirconate nanocomposites with varying compositions of Dy3+ ions were synthesized through a solution combustion method using citric acid as a fuel. There were mixed hexagonal ZnO and cubic ZrO2 phases in the X-ray diffraction patterns of the composites whose average crystallite sizes range between 27 and 38 nm. Scanning electron microscopy images show a mixture of polygonal and hexagonal rod-like structures of varying aggregation levels at the different Dy3+ -doping concentrations. The reflectance spectra showed absorption edges around 400 nm and an energy bandgap between 2.99 and 3.07 eV. There was a violet emission from the host matrix that gradually shifted towards white light with enhanced doping. At a higher Dy3+ concentration, there was luminescence quenching attributed to dipole-dipole interaction among the dopant ions. The synthesized nanocomposite phosphors may be used in sensors and colored display technology